(untitled) (Bioscience Journal, 2018)
This study evaluated the prevalence of cervicitisÂ and endometritisÂ and their interrelationsÂ in crossbred dairyÂ cowsÂ that were more than 60Â days inÂ milk (DIM), and the efficiency of the cytology techniqueÂ (cytobrush)Â andÂ histology as diagnosticÂ methodsÂ for these diseases. The reproductive tracts (n=149) derived from cows were collected from a slaughterhouse and grossly evaluated to determine uterine involution and the phase of the estrous cycle. Subsequently, cervical and uterine cytological evaluations were done to characterize the inflammatory response as cervicitis (with a neutrophilic count greater than 5%) or endometritis (with more than 6% neutrophils). Additionally, randomly obtained samples from the cervix and uterus were collected for histological evaluation. Cytological evaluation revealed that the frequency of cervicitis was 6% (9/149), and endometritis was diagnosed in 8.1% (12/149) of the samples; both inflammatory reactions were diagnosed 2.1% (3/149) in three of these. Histological evaluation revealed that of the cows diagnosed with cervicitis by cytology, 66.6% (6/9) had no inflammatory reaction in the cervical mucosa, and 33.3% (3/9) had mild inflammation in this region. Histological evaluation of the uterine horn revealed that of the 12 cows diagnosed with endometritis by cytology, 50% (6/12) of these had a histological diagnosis of mild and moderate inflammatory responses, 8.3% (1/12) of these demonstrated a severe inflammatory response, while no inflammatory reaction was identified in 41.7% (5/12) of the endometrial biopsies evaluated. In conclusion, the endometrial and cervical inflammatory response diagnosed by the cytobrush technique persisted in 12.1% of the cows. Comparatively, the frequency of the inflammatory responses at the cervix and uterus was reduced by histological analysis relative to cytological evaluation with the cytobrush technique.